Microflora of wheat (Triticum aestivum L.) in Buenos Aires Province (Argentina) and its possible significance in biological control of foliar pathogens - Perelló, Analía (2001)
Micro-organisms on the leaf surface of Triticum aestivum L. were examined. The wheat leaves were collected from experimental fields in six localities of Buenos Aires Province (Argentina). Thirteen mycelial fungi, two yeasts and a bacterium belonging to the genus Bacillus (Bw/97) were isolated from wheat foliage and evaluated for effectiveness in suppressing Alternaria triticimaculans, Bipolaris sorokiniana, Drechslera tritici-repentis and Septoria tritici under controlled conditions. Antagonistic activity was examined with the dual cultures method on potato dextrose agar media among 10 of these micro-organisms against the four foliar pathogens. Mycelial growth inhibition and colony interactions in all possible paired combinations were evaluated. The results are discussed in relation to the biological control of these cereal pathogens. In this work, the importance of indigenous antagonists in wheat disease suppression and the possibility of managing ecosystem conditions in order to enhance natural biological control is suggested. In our assays, Aspergillus niger, Bw/97 and Nigrospora sphaerica showed a strong inhibitory effect in vitro against the average of the four necrotrophic fungi tested and justify further evaluation for biocontrol of wheat foliar pathogens. The others antagonists ranked variably among the assays. Greenhouse bioassays and field evaluations using these isolates are currently under investigation.